Adjunctive radiofrequency ablation for the endoscopic treatment of ampullary lesions with intraductal extension (with video) - Suarez, Alejandro L.; Coté, Gregory A.; Elmunzer, B. Joseph (Endoscopy International Open, 2016)
Background and study aims: Catheter-based radiofrequency ablation (RFA) delivered during endoscopic retrograde cholangiopancreatography (ERCP) may represent a viable treatment option for intraductal extension of ampullary neoplasms, however, clinical experience with this modality is limited. After ampullary resection, 4 patients with intraductal extension underwent adjunctive RFA of the distal bile duct. All patients received a temporary pancreatic stent to reduce the risk of pancreatitis, as well as a plastic biliary stent to prevent biliary obstruction. Three patients were treated for adenoma and 1 for adenoma with a focus of adenocarcinoma. During a short follow-up period, 3 patients experienced complete eradication of the target lesion, whereas the patient with a focus of adenocarcinoma had progression to overt invasive cancer. There were no immediate adverse events. One patient developed a post-RFA bile duct stricture, which has required additional endoscopic therapy. Catheter-based RFA of ampullary lesions that extend up the bile duct is technically feasible. Additional research is necessary to understand the risks and long-term benefits of this technique.